2008
DOI: 10.1086/592429
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Iron Line Emission from the Neutron Star Low‐Mass X‐Ray Binary 4U 1636‐536

Abstract: We present an analysis of XMM-Newton and RXTE data from three observations of the neutron star LMXB 4U 1636-536. The X-ray spectra show clear evidence of a broad, asymmetric iron emission line extending over the energy range 4Y9 keV. The line profile is consistent with relativistically broadened Fe K emission from the inner accretion disk. The Fe K line in 4U 1636-536 is considerably broader than the asymmetric iron lines recently found in other neutron star LMXBs, which indicates a high disk inclination. We f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
97
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(109 citation statements)
references
References 28 publications
10
97
2
Order By: Relevance
“…Sometimes, in highly inclined sources, broad iron emission lines were found together with highly ionized iron lines in absorption, clearly indicating the presence of an out-flowing disk wind (see, e.g., the case of the bright atoll source GX 13+1; Pintore et al 2014, and references therein). In the case of 4U 1636-536, Pandel et al (2008) tentatively fitted the very broad emission feature present in the range 4 − 9 keV with a combination of several Kα lines from iron in different ionization states. In particular they fitted the iron complex with two broad emission lines with centroid energies fixed at 6.4 and 7 keV, respectively.…”
Section: The Combined Xmm-newton and Integral Spectrummentioning
confidence: 95%
“…Sometimes, in highly inclined sources, broad iron emission lines were found together with highly ionized iron lines in absorption, clearly indicating the presence of an out-flowing disk wind (see, e.g., the case of the bright atoll source GX 13+1; Pintore et al 2014, and references therein). In the case of 4U 1636-536, Pandel et al (2008) tentatively fitted the very broad emission feature present in the range 4 − 9 keV with a combination of several Kα lines from iron in different ionization states. In particular they fitted the iron complex with two broad emission lines with centroid energies fixed at 6.4 and 7 keV, respectively.…”
Section: The Combined Xmm-newton and Integral Spectrummentioning
confidence: 95%
“…This finding is partly contested by Cackett et al (2010) who fit the same spectra with a blurred reflection model that includes effects like Compton broadening and line emission from relevant elements. Cackett et al (2010) showed that fitting the spectrum with a self-consistent reflection model resulted in slightly larger values for the inner disc radius than when the spectrum was fit with the phenomenological diskline model (Fabian et al 1989) used by Pandel et al (2008). Nonetheless, both the results of Pandel et al (2008) and Cackett et al (2010) are based on data which were not corrected for pileup effects.…”
Section: U 1636-53mentioning
confidence: 99%
“…As demonstrated by Ng et al (2010), re-analyses of the same XMM-Newton data considering pileup and background effects, suggested a different iron line profile. Ng et al (2010) found that the Fe lines in the three spectra of 4U 1636-53 used by Pandel et al (2008) appeared to be symmetric and could be well fit with a Gaussian profile, although, due to the statistics, a relativistic origin of the line could not be excluded. However, Ng et al (2010) did not include the simultaneous RXTE data in their fits, which can affect the Fe emission line profile that strongly depends on the underlying continuum.…”
Section: U 1636-53mentioning
confidence: 99%
See 2 more Smart Citations